2015
DOI: 10.1155/2015/806151
|View full text |Cite
|
Sign up to set email alerts
|

Halo Evolution of Hypereutectic Al‐17.5Si Alloy Treated with High‐Current Pulsed Electron Beam

Abstract: Halo evolution of an Al-17.5Si alloy surface after treatment with increasing pulse numbers of a high-current pulsed electron beam (HCPEB) was investigated. A halo is a ring microstructure resembling a bull’s eye. SEM results indicate that the nanocrystallization of halo induced by HCPEB treatment leads to gradual diffusion of the Si phase. Multiple pulses numbers cause the Si phase to be significantly refined and uniformly distributed. In addition, nanosilicon particles with a grain size of 30~100 nm were form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…Figure 3b indicates that many micro nano-eutectic silicon phases (5-20 nm) formed near the edge of the crater structures. This phenomenon confirms the findings in [16]. The nano-crystallites were identified as Si by the corresponding SAED pattern.…”
Section: Sem Analysis Of the Surface Morphologysupporting
confidence: 90%
“…Figure 3b indicates that many micro nano-eutectic silicon phases (5-20 nm) formed near the edge of the crater structures. This phenomenon confirms the findings in [16]. The nano-crystallites were identified as Si by the corresponding SAED pattern.…”
Section: Sem Analysis Of the Surface Morphologysupporting
confidence: 90%
“…The corresponding evidence is that the Al phase exists around the nano-primary Si phase. The diffusion phenomenon of Al has been confirmed elsewhere via SEM and EPMA analyses [36,39]. It is concluded that Al gradually permeates into the primary Si phase because of the rapid heating effect induced by HCPEB.…”
Section: Microstructure Analysis Under Hcpeb Irradiationmentioning
confidence: 57%
“…Mg and Si tend to diffuse outwards because of the element diffusion effect induced by HCPEB. Essentially, the alloying elements diffuse along the chemical element gradient by virtue of this effect, thus eventually leading to a homogenous distribution of the elements [36,39]. The surface components of the alloys become homogenous at high pulse numbers, thus improving the surface properties of the materials.…”
Section: Microstructure Analysis Under Hcpeb Irradiationmentioning
confidence: 99%
“…In previous studies [16,17], our group found that the unmodified Al-17.5Si alloy was refined into the nano-primary silicon phase because of the rapid heating and cooling effects of HCPEB. Rare earths, as an excellent modifier, can induce spheroidization of the silicon phase.…”
Section: Morphology Analysismentioning
confidence: 99%